How does creativity at work influence employee's positive affect at work? - Tavares, S. M. (European Journal of Work and Organizational Psychology, 2016)
Although determinants of creativity underlying innovative behaviour at work have been extensively studied, scant research has addressed creativity as a predictor variable. This paper proposes that creativity has a positive impact on employees’ positive affect at work. Two studies were conducted. Study 1 used multi-source data (170 employee-supervisor dyads) to analyse the association between creativity at work, rated by the immediate supervisor, and employees’ reported affect at work. Results showed that creativity at work is positively related to positive affect at work over and above employees’ optimism (dispositional trait). Study 2 replicated and extended these findings using two-wave data from 108 high-school teachers. Results evidenced that employees who were more creative at work (T1) were more likely to report having more frequent positive affect at work 3 months later (T2). The level of meaningfulness of work (T1) mediated the effects of creativity on employees’ positive affect at work. These findings provide evidence for framing creativity in the workplace as a meaningfulness-making activity that affects employees’ positive affect at work. The implications of these findings and areas for future research are discussed.